First-principles calculation to investigate the viability of Cu-doped MoS2 for terahertz photodetection - Ducut, Melsa Rose D. (Animo Repository, 2025)
First-principles calculations were conducted using Quantum Espresso to investigate the effect of doping monolayer molybdenum disulfide (MoS2) with Cu on its structural, electronic, and optical properties. A 5×5 supercell was assembled with a total of 75 atoms. In the case of the pristine MoS2, there are 25 Mo and 50 S atoms in the supercell. To simulate doping, Mo/S atoms were replaced with Cu. Results showed that Cu doping changes the material from an n-type semiconductor into a p-type semiconductor by shifting the Fermi energy level towards the valence band in all variations of concentration and site. Moreover, the electron mobility calculations show that doping MoS2 by increasing the total charge up to 0.4e can increase electron mobility, enabling its more effective use for terahertz applications. The absorption coefficient, photoconductivity, and reflectivity calculations indicate that Cu-doped MoS2 is sensitive to violet light. In addition, Cu doping elevates the sensitivity of the material to low-energy light. These results show that Cu-doped MoS2 can be used in optoelectronic applications.